Kontekstualisasi Pendayagunaan Zakat di Badan Amil Zakat Nasional (BAZNAS) Kota Pekanbaru Berdasarkan Undang-Undang No. 23 Tahun 2011 Tentang Pengelolaan Zakat - Triana, Yeni; Basri, Hasan; Azani, Muhammad (Jurnal Hukum Novelty, 2018)
Article 27 Paragraph (1) and (2) Â Â Law of 23 Year 2011 on management of zakat states that zakat can be empowered for the weak economic community. This article discusses contextualization, contextualization efforts, obstacles and efforts to overcome the constraints of the contextualization of utilization of zakat in Baznas Pekanbaru City based on Law of 23 2011 on Zakat Management. The results showed that the contextualization of utilization of zakat in Baznas Pekanbaru City is ijtihad conducted by amil zakat in an effort to increase the prosperity of mustahik zakat into muzaki. Article 27 Paragraph (1) and Paragraph (2) above make no clear mention of appropriate models, patterns and mechanisms regarding the utilization of zakat in the sense of empowerment, so that the contextualization ijtihad conducted by Baznas Pekanbaru City is very different from the pattern of zakat utilization in the other region. Contextualization effort is an effort to change the mindset of zakat mustahik from consumptive to be productive in accordance with the purpose of substance of zakat. These efforts should be followed with appropriate and appropriate targeted patterns of community empowerment. Contextualization efforts should have a roadmap (roadmap) as a guide for the implementation of zakat utilization. The Strategy conducted by Baznas Pekanbaru City in carrying out the above efforts is to development zakat community based or zakat community development. Obstacles and efforts to be done in overcoming these barriers are, first, the lack of public awareness in zakat, thus, its lack understanding should be overcomed by increasing the socialization of true rule (fiqh) of zakat. Second, the lack of qualified human resources should be overcomed by increasing the well understanding of zakat for amil zakat, its management, and its empowerment. Third, the inadequate barriers about zakat information systems have resulted in unintegrated of the mustahik and muzaki database, that is why, it should be complemented with the updated integration of zakat management information system.